Mendelian randomization of chronic hepatitis B and cardiovascular disease - Wu, Dongjie; Xiong, Feiyang; Ran, Qingzhi; Liu, Jing; Wu, Qingjuan; Wang, Liang; Lv, Wenliang (Frontiers in Cardiovascular Medicine, 2024)
Abstract Background: Evidence from observational studies suggests that chronic hepatitis B (CHB) is associated with cardiovascular disease (CVD). However, results have been inconsistent and causality remains to be established. We utilized two-sample Mendelian randomization (MR) to investigate potential causal associations between CHB and CVD, including atherosclerosis, coronary heart disease, hypertension, and ischemic stroke. Methods: The analysis was conducted through genome-wide association studies (GWAS), considering chronic hepatitis B as the exposure and cardiovascular disease as the endpoint. The primary method for evaluating causality in this analysis was the inverse-variance weighted (IVW) technique. Additionally, we employed the weighted median, MR-Egger regression, weighted mode, and simple mode methods for supplementary analyses. Finally, heterogeneity tests, sensitivity analyses, and multiple effects analyses were conducted. Results: In a random-effects IVW analysis, we found that genetic susceptibility to chronic hepatitis B was associated with an increased risk of atherosclerosis (OR=1.048,95%CI[1.022-1.075],P=3.08E-04), as well as an increased risk of coronary heart disease (OR=1.039,95%CI[1.006-1.072],P=0.020). However, it was found to be inversely correlated with ischemic stroke risk (OR=0.972,95%CI[0.957-0.988],P=4.13E-04). There was no evidence that chronic hepatitis B was associated with hypertension (OR=1.021,95%CI[0.994-1.049],P=0.121). Conclusion: Our research indicates that chronic hepatitis B has a correlation with an elevated risk of developing atherosclerosis and coronary heart disease, while it is associated with a decreased risk of experiencing an ischemic stroke.